Report of the task force on tax administration - federal republic of Nigeria (Lagos Federal republic of Nigeria, 1979)
This handbook is a compilation of the task force reports on tax administration. The paper reveals some of the basic principles, guidelines, policies and procedures in the management and collection of various tax.
asm; 10/04/19
Loans
Keywords: Tax administration; Nigeria